Neuropsychiatric phenotype of post COVID-19 syndrome in non-hospitalized patients - Lier, Julia; Stoll, Kristin; Obrig, Hellmuth; Baum, Paul; Deterding, Lea; Bernsdorff, Nora; Hermsdorf, Franz; Kunis, Ines; Bräsecke, Andrea; Herzig, Sabine; Schroeter, Matthias L.; Thöne-Otto, Angelika; et al. (Frontiers in Neurology, 2022)
The post COVID-19 syndrome (PCS) is an emerging phenomenon worldwide with enormous socioeconomic impact. While many patients describe neuropsychiatric deficits, the symptoms are yet to be assessed and defined systematically. In this prospective cohort study, we report on the results of a neuropsychiatric consultation implemented in May 2021. A cohort of 105 consecutive patients with merely mild acute course of disease was identified by its high symptom load 6 months post infection using a standardized neurocognitive and psychiatric-psychosomatic assessment. In this cohort, we found a strong correlation between higher scores in questionnaires for fatigue (MFI-20), somatization (PHQ15) and depression (PHQ9) and worse functional outcome as measured by the post COVID functional scale (PCFS). In contrast, neurocognitive scales correlated with age, but not with PCFS. Standard laboratory and cardiopulmonary biomarkers did not differ between the group of patients with predominant neuropsychiatric symptoms and a control group of neuropsychiatrically unaffected PCS patients. Our study delineates a phenotype of PCS dominated by symptoms of fatigue, somatisation and depression. The strong association of psychiatric and psychosomatic symptoms with the PCFS warrants a systematic evaluation of psychosocial side effects of the pandemic itself and psychiatric comorbidities on the long-term outcome of patients with SARS-CoV-2 infection.